Analysis of Teaching Module in Merdeka Curriculum Used by Teacher in Chemistry Learning at SMAN 10 Pontianak - Wilda, Wilda; Hairida, Hairida; Sasri, Risya; Masriani, Masriani; Ulfah, Maria (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Teaching modules are learning tools in the merdeka curriculum. The aim of this research is to analyze the merdeka curriculum teaching modules used by educators in teaching chemistry. Quantitative descriptive methods were used in this research, and data collection techniques used measurement and documentation. The data collection tool is a learning tool review sheet that has been validated by two experts using the Gregory test. The object studied was the merdeka curriculum teaching module used by class X chemistry educators at SMAN 10 Pontianak in a total of six meetings. Data analysis was carried out based on scores on each component of the teaching module. Based on the data obtained from the analyzed teaching module components, it obtained a score of 88.3 and was included in the good category. Thus, it can be concluded that the components contained in the teaching module are in accordance with the merdeka curriculum learning and assessment guidelines, and the module is good for use in learning activities.